Multi-channel recovery data flow parallel transmission and control method - ZHANG Bing1; LU Zheng-tian2; LI Tao2 (Tongxin xuebao)
In order to shorten the time for disaster recovery, a multi-channel recovery data flow parallel transmission and control（MRPTC）method was presented.First, the connections between the server to be recovered and the several standby servers were established, the difference comparison between the current damaged data and the original intact data（the backup data） was completed, the differences were obtained.Then the different parts of the differences were dynamically downloaded from the standby servers in the parallel mode, these parts were united locally, the whole data was finally obtained, and the fast disaster recovery of the data was achieved.The theoretical analysis and the experiment results show that the proposed method has the features of multi-point collaborative difference recovery, high recovery speed, full bandwidth utilization, and low network requirement.Therefore, this method is a new good approach of fast disaster recovery.